Influence of Residualizing Properties of the Radiolabel on Radionuclide Molecular Imaging of HER3 Using Affibody Molecules - Rinne, Sara S. (Int J Mol Sci, 2020)
Human epidermal growth factor receptor type 3 (HER3) is an emerging therapeutic target in several malignancies. To select potential responders to HER3-targeted therapy, radionuclide molecular imaging of HER3 expression using affibody molecules could be performed. Due to physiological expression of HER3 in normal organs, high imaging contrast remains challenging. Due to slow internalization of affibody molecules by cancer cells, we hypothesized that labeling (HE)(3)-Z(HER3:08698)-DOTAGA affibody molecule with non-residualizing [(125)I]-N-succinimidyl-4-iodobenzoate (PIB) label would improve the tumor-to-normal organs ratios compared to previously reported residualizing radiometal labels. The [(125)I]I-PIB-(HE)(3)-Z(HER3:08698)-DOTAGA was compared side-by-side with [(111)In]In-(HE)(3)-Z(HER3:08698)-DOTAGA. Both conjugates demonstrated specific high-affinity binding to HER3-expressing BxPC-3 and DU145 cancer cells. Biodistribution in mice bearing BxPC-3 xenografts at 4 and 24 h pi showed faster clearance of the [(125)I]I-PIB label compared to the indium-111 label from most tissues, except blood. This resulted in higher tumor-to-organ ratios in HER3-expressing organs for [(125)I]I-PIB-(HE)(3)-Z(HER3:08698)-DOTAGA at 4 h, providing the tumor-to-liver ratio of 2.4 ± 0.3. The tumor uptake of both conjugates was specific, however, it was lower for the [(125)I]I-PIB label. In conclusion, the use of non-residualizing [(125)I]I-PIB label for HER3-targeting affibody molecule provided higher tumor-to-liver ratio than the indium-111 label, however, further improvement in tumor uptake and retention is needed.